Intervention model in organizational climate - Lucila Cárdenas Niño (Universidad de San Buenaventura, 2009)
The aim of this study was to assess whether the intervention model in organizational climate PMCO, was effective in the Hospital of Yopal, Colombia. The following five phases, proposed by the model, were implemented: 1) problem analysis, 2) awareness, 3) strategies design and planning, at the individual, intergroup, and organizational levels, 4) implementation of the strategy, and 5) process evaluation. A design composed of two groups, experimental and control, was chosen, analyzing whether there was significant differences between the means of the groups; the t test was applied to high risk dimensions in the organizational climate, such as level of work (t = 2.65), organizational communication (t = 4.32), and the management model (t = 7.99), showing all of them a significant difference (p = ,01) between experimental and control group. It is concluded that the implementation of this model improved the organizational climate in the entity.